Therapeutic potential of mesalamine-probiotic combination in enteric-coated tablet for modulating gut inflammation in IBD - Pratiksha A. Thete; Milind P. Wagh; Vandana S. Nade (Creative Pharma Assent, 2026)
Background: Mesalamine is widely used for inflammatory bowel disease (IBD) due to its local anti-inflammatory action, while probiotics help restore intestinal microbiota and modulate immune responses. Combining both may offer synergistic benefits for IBD management. This study aimed to develop and evaluate colon-targeted enteric-coated tablets containing a mesalamine-probiotic combination. Methodology: Core tablets containing mesalamine, selected probiotics, and polymers were prepared by dry granulation. Pre- and post-compression parameters were evaluated. The optimized batch was coated with Eudragit® S100 (2–5%) to achieve pH-dependent release. In vitro dissolution and probiotic viability in simulated gastric conditions were assessed. Result and Discussion: The optimized formulation showed acceptable physical properties and negligible drug release in gastric pH, followed by targeted colonic release exceeding 90% at intestinal/colonic pH. Mesalamine release followed Higuchi kinetics, suggesting diffusion-controlled behavior. Swelling studies demonstrated gradual polymer hydration and matrix erosion. Probiotic viability studies demonstrated strain-dependent survival: Saccharomyces boulardii and Streptococcus thermophilus retained>90% viability after 150 min of simulated gastric exposure, whereas Lactobacillus acidophilus and Bifidobacterium bifidum exhibited approximately 1.2–1.3 log reductions, indicating greater acid sensitivity. The combination of enteric coating enabled efficient colon targeting and sustained release. Differential strain viability emphasized the importance of selecting acid-resistant probiotics or employing protective delivery systems. Conclusion: The developed mesalamine–probiotic enteric-coated tablets demonstrated colon-specific drug release and strain-dependent probiotic survival in vitro, indicating their potential as a candidate formulation requiring further optimization, particularly for acid-sensitive bacterial strains.